2009
DOI: 10.1002/pamm.200910314
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Drug Dissolution Rates in the USP 24 Type 2 Apparatus

Abstract: This paper applies boundary layer theory to the process of drug dissolution in the USP 24, Type 2 Apparatus. The mass transfer rate from the top flat surface of a compact in various positions within the device is evaluated by means of a Pohlhausen integral method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Literature data also showed that floating during dissolution led to higher standard deviation of the result [28] . This is confirmed by hydrodynamic studies performed by D'Arcy and co-workers demonstrating less variability in dissolution data from tablets fixed to a single position compared with those that were not fixed [46,48] . For porous tablets that float during dissolution, using basket method, in our case, did not improve the reproducibility of the in vitro release data (as seen in Supplementary Materials Figure S4).…”
Section: Figure S3supporting
confidence: 69%
“…Literature data also showed that floating during dissolution led to higher standard deviation of the result [28] . This is confirmed by hydrodynamic studies performed by D'Arcy and co-workers demonstrating less variability in dissolution data from tablets fixed to a single position compared with those that were not fixed [46,48] . For porous tablets that float during dissolution, using basket method, in our case, did not improve the reproducibility of the in vitro release data (as seen in Supplementary Materials Figure S4).…”
Section: Figure S3supporting
confidence: 69%